Tobit - Ego, Beate (W. Kohlhammer GmbH, 2022)
This commentary places the ancient Jewish Tobit narrative in the broader context of the history of the tradition by analysing both the ideas it contains about ancient medicine and its conception of the Torah. It also presents a synchronic overall interpretation showing that the narrative is ultimately to be understood in terms of the theology of history. It explaines lucidly the way in which ancient Judaism was able to engage with the threat posed by the aggressive policies of the great empires during the period of Hellenistic rule. In this context, the hymn of praise by the aged Tobit at the end of the narrative in Tob. 13 opens up prospects of hope for those to whom it is addressed. Diese Kommentierung stellt die antikjüdische Tobiterzählung in einen breiten traditionsgeschichtlichen Kontext, indem sie sowohl die darin enthaltenen Vorstellungen zu Engeln und Dämonen sowie zur antiken Medizin als auch ihre Torakonzeption analysiert. Außerdem wird eine synchron ausgerichtete Gesamtinterpretation vorgelegt, die zeigt, dass die Erzählung letztlich geschichtstheologisch zu verstehen ist. Sie macht deutlich, wie sich das antike Judentum in der Zeit der hellenistischen Herrschaft mit der Bedrohung durch die aggressive Politik der Großreiche auseinandersetzen konnte. Der Lobgesang des alten Tobit am Ende der Erzählung in Tob 13 eröffnet in diesem Kontext eine Hoffnungsperspektive für ihre Adressaten